Morphological Differentiation of Ventral Tarsal Setae and Surface Sculpturing of Theraphosids (Araneae: Theraphosidae) With Different Types of Lifestyles. (12th February 2022) - Szymkowiak, Paweł; Grabowski, Patryk
Abstract: The ventral surfaces of tarsi in spiders in the infraorder Mygalomorphae group play a key role in locomotion and burrow and nest construction. In our research, we analyzed the diversity of setae and patterns of sculpturing on tarsi in three species with different life strategies: a burrowing spider Brachypelma smithi (F. O. Pickard-Cambridge, 1897), a ground-dwelling spider, Pterinochilus murinus Pocock, 1897, and a arboreal spider, Poecilotheria regalis Pocock, 1899. We showed the presence of three types of setae on the ventral side of tarsi: plumose setae, short-haired spiniform setae, and spirally striated setae. Plumose setae were differentiated within a tarsus and their apical sections among the studied species, while the microtriched ensiform and spirally striated setae did not differ. All setae were characterized by a similar structure. Little differentiation was observed in the number and location of setae on the tarsi of the studied species. Spirally striated setae were absent in the burrowing spiders. In contrast, the shape and size of the sculpturing pattern varied among the studied species. The greatest differentiation was found in the burrowing and ground-dwelling spiders, while the smallest differentiation was found in the arboreal spider. We discuss our findings in relation to preferred habitats, the biology of the spiders, and adaptation of sculpturing and setae on spider feet to surface type. The morphology and diversity of setae and sculpturing patterns on the ventral side of tarsi in P. murinus was reported for the first time .